Factors Affecting The Performance of Indonesian Specialty Food SMEs in South Tangerang - Nur Hidayah; Rodhiah Rodhiah (International Journal of Management Science and Application, 2025)
A common metric for assessing how a company's strategy affects competition is business performance.  In contrast to their current competitors, businesses must highlight the competitive advantages of their products and pursue market orientation and innovation to boost performance.  The goal of this study is to gain a thorough understanding of the factors that influence the performance of small and medium-sized businesses (SMEs) in the Tangerang Selatan region that produce speciality Indonesian goods.  The purpose of this study is to ascertain if business strategy is influenced by entrepreneurial orientation and how environmental dynamics affect the performance of SMEs in South Tangerang that produce Indonesian specialty foods.  Purposive sampling is the method used to select the sample for this study. Questionnaires were distributed to sample participants who were based in Tangerang to gather data.  This method of data analysis combines Smart PLS with SEM.  The study's findings indicate that, among small and medium-sized businesses in South Tangerang that produce Indonesian speciality foods, entrepreneurial orientation has a positive and significant impact on business performance, business strategy has a negative and negligible impact, and environmental dynamics have a positive and significant impact.